The Substitute Millionaire - Footner, Hulbert, 1879-1944 (Salt Lake City, UT : Project Gutenberg, 2018)
"The Substitute Millionaire" by Hulbert Footner is a novel written in the early 20th century. The story introduces us to Jack Norman, a bookkeeper living on a minimal salary, who becomes embroiled in a sensational aftermath following the murder of a wealthy miser, Silas Gyde. After an unexpected turn of events, Jack learns that he is the sole heir to Gyde$1 (Bs vast fortune, which propels him into a life filled with wealth and the trappings that come with it. The opening of the book sets the stage for Jack$1 (Bs character and his socioeconomic frustrations as he navigates daily life on a meager income. With the backdrop of Gyde's explosive demise making headlines, Jack fantasizes about a life of luxury far removed from his austere reality. His fortunes change when he is summoned by Walter Delamare, the president of the National New York Bank, who reveals that Jack has inherited millions from Gyde. The initial excitement is tempered by the heavy realization of the responsibilities that accompany such wealth, especially in light of Gyde$1 (Bs infamous life and the dangers lurking due to previous threats against him. As Jack contemplates his new wealth, he faces immediate challenges of identity, danger from those who may covet Gyde's legacy, and the complexities of romance that arise with his newfound status. (This is an automatically generated summary.)s
Release date is 2018-05-25
Produced by Al Haines
Keywords: Detective and mystery stories; Canadian fiction -- 20th century